1999
DOI: 10.1042/cs0970539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arm dominance and brachial artery cannulation on forearm blood flow measured by strain-gauge plethysmography

Abstract: The human forearm model is used extensively in physiological, pharmacological and clinical investigations. Effects of arm dominance or arterial cannulation on forearm flow measurements have never been tested formally. In the present study we tested the hypotheses that left or right arm dominance or cannulation of the brachial artery do not affect forearm haemodynamic responses to physiological or pharmacological stimuli. Results obtained in 16 volunteers showed that forearm blood flow responses to physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There is no difference in the values of flow parameters between the dominant and non-dominant sides, and therefore it is important to compare the arterial perfusion following repair, as the patient acts as their own control. 11,26 Due to the wide diameter of the brachial artery, microsurgical repair is not absolutely necessary, however, as it is an atraumatic technique we would expect to see better patency compared to macrovascular techniques especially in the early period following repair. 6 -9 In the late follow-up period, as in our study, the effect of anastomosis technique is questionable because in a high proportion of cases there is relative stenosis due to widening of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…There is no difference in the values of flow parameters between the dominant and non-dominant sides, and therefore it is important to compare the arterial perfusion following repair, as the patient acts as their own control. 11,26 Due to the wide diameter of the brachial artery, microsurgical repair is not absolutely necessary, however, as it is an atraumatic technique we would expect to see better patency compared to macrovascular techniques especially in the early period following repair. 6 -9 In the late follow-up period, as in our study, the effect of anastomosis technique is questionable because in a high proportion of cases there is relative stenosis due to widening of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusion was reached by Kamper and Chang when they investigated the effects of arm dominance on forearm blood flow measured by strain-gauge plethysmography. They suggested that left or right arm dominance does not determine forearm vascular responses to physiologi- cal tests and that either arm can be used as the control or the study arm [28].…”
Section: Discussionmentioning
confidence: 99%